Digital infographics as a dynamic information-transfer model for academic discourse in language classroom - Wan Najmiyyah Wan Md Adnan; Norhayati Husin; Nooryuhanis Hashim; Roszainora Setia (Penerbit Universiti Kebangsaan Malaysia, 2024)
The integration of digital infographics in language classrooms has developed into an innovative approach to promote academic discourse and student engagement. However, given the limitations of traditional teaching methods, there is a need to improve student engagement and information transfer in language classrooms. This study explores the potential use of digital infographics as an information-transfer model for academic discourse. It aims to answer two primary research questions: 1) What are the features of digital infographics used by students to organise and deliver information during language classroom discourse? and 2) How can teachers help students use digital infographics in classroom discourse? A qualitative research design was employed. 44 students reviewed selected documentaries, created digital infographics, and presented their reviews to small groups of students. The digital infographics were then collected and analysed by two experienced raters. Coding was used to systematically categorise the data. The thematic areas emerged from the data were then explored. The findings indicated that information organisation, as well as the aesthetics and functionality of the digital infographics, are features that should be included when considering digital infographics as an information-transfer model for language classrooms. This study then identified teaching strategies to help students use digital infographics in classroom discourse. The study proposes Digital Infographics Information-Transfer Model (DITRAM) to facilitate the effective integration of digital infographics in the language classroom. In conclusion, the study provides a better understanding of how digital infographics can be structured and used to convey information in academic discourse in the language classroom.